Effects of rational emotive behaviour and relaxation therapies on management of test anxiety among students with hearing impairment in Ibadan, Oyo state, Nigeria (2016)
Test taking becomes a tensed competition among students, particularly, students with hearing impairment who suffer significant academic setback, struggle hard with their hearing counterparts in test taking, creating varying degrees of test anxiety among this category of students. Thus, it became imperative to seek therapy that can best manage test anxiety among students with hearing impairment. This study therefore, examined the effect of rational emotive behaviour (REBT,) and relaxation (RT) therapies on test anxiety management among students with hearing impairment. The study adopted a pretest-posttest control group quasi-experimental research design with 3x2x2 factorial matrix. The study was conducted in 3 schools for students with hearing impertinent within Ibadan metropolis. 60 students were purposively select Jar the study. Each study group was pretested with English language achievement test at first session and post tested at last session to get the effectiveness of the treatments. Seven hypotheses were tested at 0.05 level of significance. Data were analyzed using analysis of covariance (ANCOVA,), scheffe post-HOC was used to establish the area of significance. Both REBT and RT were found to be effective in reducing test anxiety among students with hearing impairment. (F(2,36) = 20.668 P< .05, = .605). Gender among students with hearing impairment as represented in the result, (F(J3? = 6.597 P<.05,ul2=.196,) and (F0,37) — 4.498, P <.05, = .143) respectively. There was no significant main or interaction effect of treatment on gender and academic self-concept among the participants. It was concluded that both REBT and RT were good in reducing test anxiety among students with hearing impairment. Therefore, it was recommended that teachers and stakeholders should employ the use of REBT and RT in reducing test anxiety among students with hearing impairment. Positive academic self- concept should be enhanced among these students.